Covid-19 y su incidencia en el desarrollo de ansiedad infantil en un niño de 8 años de edad en la Unidad Educativa Replica Eugenio Espejo - Fajardo Pinto, Adriana Patricia (2022)
The present case study was carried out with the objective of identifying, through Rational Emotive Therapy, if COVID 19 affects the development of childhood anxiety in an 8-year-old child in the Replica Eugenio Espejo Educational Unit, the qualitative methodology that was developed in This work is aimed at determining the variables such as: COVID 19 and child anxiety which are exposed in this case study, also thanks to the implementation of the TREC techniques, it was modified that the stated objective is fulfilled in its Totality, all this was done through a therapeutic plan which contemplates an Individual Therapy procedure, aimed at modifying those thoughts that the patient expressed during the psychological intervention, in this way the symptoms in the child were reduced due to their anxiety, In this way, great results were achieved in improving their quality of life, both personal and social.